2003
DOI: 10.1007/s00259-002-1040-x
|View full text |Cite
|
Sign up to set email alerts
|

[99mTc]Demobesin 1, a novel potent bombesin analogue for GRP receptor-targeted tumour imaging

Abstract: Demobesin 1 is a potent new GRP-R-selective bombesin (BN) analogue containing an open chain tetraamine chelator for stable technetium-99m binding. Following a convenient labelling protocol, the radiopeptide, [(99m)Tc]Demobesin 1, formed in nearly quantitative yields and with high specific activities. Both unlabelled and labelled peptide demonstrated high-affinity binding in membrane preparations of the human androgen-independent prostate adenocarcinoma PC-3 cell line. The IC(50) values determined for Demobesin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
184
0
12

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 172 publications
(206 citation statements)
references
References 51 publications
(185 reference statements)
10
184
0
12
Order By: Relevance
“…After the successful use of radiolabeled somatostatin peptide analogs in neuroendocrine tumors for nuclear imaging and therapy (5,6), multiple radiolabeled GRPR radioligands have been synthesized and studied in preclinical as well as in clinical studies, mostly in prostate cancer patients. Examples of such peptide analogs include AMBA, the Demobesin series, and MP2653 (7)(8)(9)(10)(11). Recent studies have shown a preference for GRPR antagonists compared with GRPR agonists (12,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After the successful use of radiolabeled somatostatin peptide analogs in neuroendocrine tumors for nuclear imaging and therapy (5,6), multiple radiolabeled GRPR radioligands have been synthesized and studied in preclinical as well as in clinical studies, mostly in prostate cancer patients. Examples of such peptide analogs include AMBA, the Demobesin series, and MP2653 (7)(8)(9)(10)(11). Recent studies have shown a preference for GRPR antagonists compared with GRPR agonists (12,13).…”
mentioning
confidence: 99%
“…The peptidic part of NeoBOMB1, however, is based on a different GRPR antagonist first described by Heimbrook et al (17) and generated by modification of the C-terminal Leu 13 -Met 14 -NH 2 and the replacement of Asn 6 by DPhe 6 of native bombesin (6)(7)(8)(9)(10)(11)(12)(13)(14). NeoBOMB1 was chosen for further studies because of its improved affinity for the GRPR (18,19).…”
mentioning
confidence: 99%
“…Several analogs of the natural GRPr ligand bombesin, a 14-amino-acid neuropeptide, have been labeled with various radionuclides for the diagnosis and treatment of GPRrpositive tumors in recent years (8)(9)(10)(11)(12). Potent 99m Tc-based (demobesin-1) and 111 In-based (RM-1) bombesin analogs that were designed for GRPr-based targeting and tested in the PC-3 xenograft model showed high absolute tumor uptake in animals (13,14). Few publications have reported on 18 F labeling of bombesin peptides (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…However, recent reports b y N o c k e t a l ., show compelling evidence that radiopharmaceutical design and development based upon antagonist-type ligand frameworks bear reexamination (Nock et al, 2003 and. Antagonist ligands are presumably not internalized, and therefore are not expected to residualize as effectively in tumor tissue when compared to agonist-based ligand frameworks.…”
Section: Future Workmentioning
confidence: 99%
“…Antagonist ligands are presumably not internalized, and therefore are not expected to residualize as effectively in tumor tissue when compared to agonist-based ligand frameworks. Studies using 99m Tc-Demobesin1 ([ 99m Tc-N 4 0-1 ,bzlg 0 ,D-Phe 6 ,LeuNHEt 13 ,des-Met 14 ]BBN(6-14)) demonstrated very high affinity and selectivity for the GRPR with pronounced accumulation and retention of radioactivity in human tumor xenografts in rodents (Nock et al, 2003 and. In addition, Maecke and co-workers have begun investigating another antagonist-like targeting vector, [DOTA-4-amino-1-carboxymethylpiperidine-D-Phe-Gln-Trp-Ala-Val-Gly-His-Sta-Leu-NH 2 ], having high selectivity for the GRPr (Mansi et al, 2009 and2011).…”
Section: Future Workmentioning
confidence: 99%